Effect of leadership style of initiation and consideration structures toward human resources quality and budgetery planning - Cut Zulfahnur Syafitri; Nadirsyah Nadirsyah; Hasan Basri (Proceedings of AICS - Social Sciences, 2013)
Budgetary planning carried out with the involvement of many stakeholders and using a variety of resources. Nevertheless, various issues of interest have an impact on the performance of the overall budget. As such, the issues have attracted considerable research interest. Hence, the purpose of this study to empirically examine (1) the influence of leadership style of initiating structure on budgetary planning, (2) the influence of leadership style of consideration structure on budgetary planning, and (3) the influence of human resources quality on budgetary planning. The research starts by investigate respondents that were employees involved in the budgetary planning process from preparation to budget accountability at the working unit within Syiah Kuala University in Banda Aceh. This is followed by path analysis method to find out the influence of independent variables on budgetary planning using path analysis. In so doing, the results showed that (1) simultaneously leadership style of initiating structure, leadership style of consideration structure and human resources quality have a positive and significant impact on budgetary planning. (2) Testing on an individual basis, only the leadership style of consideration structure that has a strong influence positively and significantly to the budgetary planning, while leadership style of initiating structure and human resources quality affect positively and significantly but weakly to budgetary planning.Keywords: Budgetary planning, leadership style, and human resources quality